Multi-Decadal Change in Reef-Scale Production and Calcification Associated With Recent Disturbances on a Lizard Island Reef Flat - Pisapia, Chiara; Hochberg, Eric Jeremy; Carpenter, Robert (Frontiers in Marine Science, 2019)
Climate change is threatening the persistence of coral reef ecosystems resulting in both chronic and acute impacts which include higher frequency and severity of cyclones, warming sea surface temperatures, and ocean acidification. This study measured net ecosystem primary production (NEP) and net ecosystem calcification (NEC) on a reef flat after the most severe El Nino-driven mass bleaching event on Australia’s Great Barrier Reef (GBR) in 2016 and again in 2018 after another consecutive bleaching event in 2017. Our results indicate that reef metabolism is altered as result of both the continuing press disturbance of ocean acidification and severe pulse disturbances (cyclones and bleaching events). In 2016, NEP was within the range of values reported in past studies, however it declined in 2018. NEC over a 12-h period was lower in 2016 than 2018; but when compared with past studies there was a severe decline in daytime net calcification from 2008-2009, to 2016 followed by an increase in 2018 (but still NEC remained lower than values reported in 2008-2009). Conversely, nighttime net calcification was similar to that reported in 2009 indicating nighttime dissolution did not increase over the past decade. Overall coral cover remained stable following recent disturbances, however algal turf was the dominant benthic component on the reef flat, while calcifiers (corals and calcified algae) were minor components (< 20% of total benthic cover). This study documented changes in community function following major pulse disturbances (bleaching events and cyclones) within the context of ongoing OA at the same location over the last decade. Repeated pulse disturbances could jeopardize the persistence of the reef flat as a net calcifying entity, with the potential for cascading effects on other ecosystem services.